Peran Asosiasi Pemagangan Luar Negeri (AP2LN) meningkatkan Kualitas Program Pemagangan di Jepang - Eny Triastuti; Imron Natsir (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The study discusses the role of the Foreign Apprenticeship Association (AP2LN) in improving the quality of apprenticeship programmes in Japan. AP2LN has an important responsibility in monitoring and ensuring that Indonesian interns receive training in accordance with the established standards. Through cooperation with companies in Japan, AP2LN plays a role in improving the quality of training, enhancing the technical capabilities of the participants, and making sure that the rights of interns are protected. This research uses qualitative methods with in-depth interviews as the primary data collection tool. The results of the research show that the active role of AP2LN not only improves the skills of the interns, but also helps to strengthen the relationship between Indonesia and Japan in the field of human resource development.